2000
DOI: 10.1086/308374
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in the Far‐Infrared Background

Abstract: We compute the expected angular power spectrum of the cosmic Far Infrared Background (FIRB). We find that the signal due to source correlations dominates the shot-noise for ℓ < ∼ 1000 and results in anisotropies with rms amplitudes ( ℓ(ℓ + 1)C ℓ /2π) between 5% and 10% of the mean for l > ∼ 150. The angular power spectrum depends on several unknown quantities, such as the UV flux density evolution, optical properties of the dust, biasing of the sources of the FIRB, and cosmological parameters. However, when we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 49 publications
6
73
0
4
Order By: Relevance
“…The CIB clustering has been studied extensively, starting with Bond et al (1986Bond et al ( , 1991. Further theoretical investigation (Scott & White 1999;Haiman & Knox 2000) was stimulated by the detection of the infrared background in the COBE data (Puget et al 1996;Fixsen et al 1998), and the detection of bright "sub-millimetre" galaxies in SCUBA data (Hughes et al 1998). Subsequently, the clustering has been detected at 160 microns , at 250, 350 and 500 microns by the Balloon-borne Large Aperture Submillimeter Telescope (BLAST, Viero et al 2009;Hajian et al 2012) and at 217 GHz by SPT and ACT (Hall et al 2010;Dunkley et al 2011).…”
Section: Clustered Power From Unresolved Point Sourcesmentioning
confidence: 99%
“…The CIB clustering has been studied extensively, starting with Bond et al (1986Bond et al ( , 1991. Further theoretical investigation (Scott & White 1999;Haiman & Knox 2000) was stimulated by the detection of the infrared background in the COBE data (Puget et al 1996;Fixsen et al 1998), and the detection of bright "sub-millimetre" galaxies in SCUBA data (Hughes et al 1998). Subsequently, the clustering has been detected at 160 microns , at 250, 350 and 500 microns by the Balloon-borne Large Aperture Submillimeter Telescope (BLAST, Viero et al 2009;Hajian et al 2012) and at 217 GHz by SPT and ACT (Hall et al 2010;Dunkley et al 2011).…”
Section: Clustered Power From Unresolved Point Sourcesmentioning
confidence: 99%
“…There has been no detection to date of the anisotropies in this background, and so we have to rely on theoretical estimates (Haiman & Knox 2000;Knox et al 2001). …”
Section: Comparison To the Far-infrared Foregroundmentioning
confidence: 99%
“…Works by Farrah et al (2006) and Magliocchetti et al (2008) measured a strong clustering of ultra luminous infrared galaxies (ULIRG) detected with Spitzer at high redshifts. Alternatively, the infrared background anisotropies could also provide information about the correlation between the sources of the CIB and dark matter (Haiman & Knox 2000;Knox et al 2001;Amblard & Cooray 2007), and its redshift evolution. Lagache et al (2007) and Viero et al (2009) reported the detection of a correlated component in the background anisotropies using Spitzer/MIPS (160 μm) and BLAST (250,350, and 500 μm) data.…”
Section: Introductionmentioning
confidence: 99%